Makna Perjamuan Malam Kudus Bagi Umat Kristen Lukas 22:19-20 Sebuah Respon Atas Tuduhan Bahwa Orang Kristen Adalah Kanibal - Melda Greace; Malik Bambangan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
the liberation of the Israelites from slavery in Egypt, marking God's intervention in the history of His people and the beginning of a new grain harvest. On the other hand, Easter marks the resurrection of Jesus Christ, a symbol of victory over sin and death, and the culmination of salvation provided through His sacrifice on the cross. In this context, the Eucharist becomes an important sacrament symbolizing the body and Passover and Easter have deep meanings in their respective religious traditions. Passover (Pesach) celebrates blood of Christ. The bread, as a symbol of His broken body, and the cup, as a symbol of His shed blood, remind Christians of God's infinite sacrifice and love. However, in the early days of Christianity, the practice of the Eucharist was often misunderstood, leading to accusations of cannibalism against Christians. This misunderstanding arose because the terms